Status and distribution of the Common Shelduck Tadorna tadorna in Iceland, with special reference to the core area in Borgarfjörður - Tierney, Niall; Tierney, Rachel A.; Björnsson, Þorvaldur; Kolbeinsson, Yann; Townsend, Sunny E.; Petersen, Aevar (Wildfowl, 2020)
The Common Shelduck Tadorna tadorna was first recorded as a breeding bird in Iceland in 1990. Since then, local monitoring programmes and casual observations suggest that the population has expanded in range and abundance, but a detailed overview of its breeding locations and the total number of birds recorded has not been compiled to date. We therefore investigated the size and distribution of the Icelandic population by collating information from published literature and from personal observations by the authors and birdwatchers (eBird, social media, emails) reported between 1990 and 2019 inclusive. At the core breeding area in Borgarfjörður (western Iceland), low and rising tide surveys were conducted each week between 12 March and 25 October 2017 to investigate spring arrival times, overall numbers and site usage. The number of breeding pairs was estimated from the number of broods observed in June and July. The Icelandic population was estimated at 274 breeding pairs. Borgarfjörður continues to support the biggest aggregations, and the most breeding pairs (158 pairs, c. 60% of the Icelandic breeding population). The next most important areas are Breiðafjörður (northwest Iceland) and Melrakkaslétta (northeast Iceland) (c. 20 pairs each). The first arrivals in Borgarfjörður were recorded on 12 March. Birds were present throughout the survey period and 100 birds remained on the last survey on 25 October. A high count of 1,368 Shelducks was recorded on 26 June. The tidal state, subarea and week of the survey each had a significant effect on Shelduck numbers. This study shows that the population has grown exponentially and there has been a considerable expansion in breeding range. A coordinated national survey is required to assess the population size and range more accurately. The relatively large numbers, and the proportion of the national population that occurs in Borgarfjörður, make it an attractive site for further research on these birds: on their wintering and moulting areas, productivity, diet and survival rates.